The effect of exchange rate fluctuations on the Economic growth Analytical study on Libya (1980-2015) (Comprehensive Journal of Science, 2026)
T his study primarily aims to examine the impact of fluctuations in the real exchange rate of the Libyan dinar against the dollar on economic growth, using annual data covering the period from 1980 to 2015. To achieve this, a standard model was designed based on economic theories and published scientific studies. Appropriate econometric analysis methods and tests were also used. Data were obtained from the World Bank (WB), the Central Bank of Libya, and the Center for Economic Sciences Research.The results of the econometric analysis of the model revealed a statistically significant negative impact of the real exchange rate variable on economic growth in Libya. In light of the findings, the study recommends the need to control unproductive spending by using both monetary and fiscal policies to achieve monetary stability, especially exchange rate stability, increasing the trend towards encouraging local and foreign investment and directing imports towards developmental and productive goals in order to reduce the impact of real exchange rates on increasing inflation rates, increasing local production, diversifying it and improving its quality to create a competitive situation in terms of quality and prices, and reducing the degree of dependence on a single commodity for export and the resulting various problems, and consequently a decrease in the gross domestic product
Keywords: Exchange rate - GDP - Economic growth - Exports